The importance of the heritage values of Al-Ukhaidhir palace, Karbala city, Iraq - Akram, Omar Khasro; Mohammed Jamil, Nada F; Ismail, Sumarni; J Franco, Daniel; Graca, Andreia (Institute of Physics Publishing, 2018)
Karbala is distinguished by its rich architectural heritage. Deterioration of historic buildings can affect the city itself as well as the country as general. This research highlights the issue that Al-Ukhaidhir palace, located in Karbala city, is facing. There is no attention from local population, neither experts to protect the architectural heritage values of Al-Ukhaidhir palace. Therefore, there is a dire need for an action to protect the historical palace, aiming to save it for next generations and to increase tourism not just in the city, but for the country in general. After the introduction of the background problem, this study presents a literature review on Al-Ukhaidhir Palace, highlighting their significant heritage values and then summarizing the issues that are presently putting Al-Ukhaidhir Palace into danger. The methodology of this research is based in a case study, which follows a Qualitative method. This study contributes in identification of the significant values of the palace, proposing a theory on the protection of Islamic Architecture Heritage, from the issues that Al-Ukhaidhir Palace in Karbala City is facing and highlights the important role of experts and local population in the preservation process of heritage sites with its recommendations. It helps on the protection and documentation of heritage values in Al-Ukhaidhir Palace, having a global impact towards humanity issues.